Dixit mihi unam gravem villaniam, quam non possum dicere: Patterns of Verbal Insult, Social Hierarchy, and Concept of Honour in Medieval Ragusa - Marinković, Ana (2009)
The urban community of medieval Ragusa by no means did lack in personal conflicts, but the high level of social order was evident in a rather developed system of regulative norms concerning various types of assaults. The detailed